Bahasa Minoritas Hamap dalam Perkebunan Jagung: Tinjauan Etnolinguistik - Fanny Henry Tondo (Jurnal Pendidikan dan Kebudayaan, 2012)
This objective of this article is to analyze the linguistic forms used by Hamap people in a corn plantation. This qualitative study is interdisciplinary, because it combines two scientific disciplinaries,namely linguistics and anthropology (ethnolinguistics). Based on this perspective, it is found that in this modern era Hamap people still retain their original traditions. The traditions can be found in the corn plantation which is expressed by the names of plantation tools, corn and its traditional names, the process of corn plantation, and traditional songs accompanying the corn planting process. These linguistic forms implicitly describe that although Hamap language is minor and includes potential endangered language it is still used in the corn plantation